Light hydrocarbons composition and carbon isotopes unravel the origin of natural gas in Triassic marine strata of Moxi gas field, central Sichuan Basin - Guo, Chuyuan; Hu, Guoyi; Li, Jin; Tian, Xingwang; Tian, Lianjie; Guo, Jinhao; Cui, Huiying; Liu, Zhen; Li, Xianqing (Frontiers in Earth Science, 2025)
The Triassic marine gas reservoir in the Moxi Gas Field is one of the large gas fields initially discovered in the Sichuan Basin. However, the origin of its natural gas has long been debated. To study the genetic types and origin of natural gas, the light hydrocarbons (LHs) composition, carbon isotopes, chemical compositions, and stable carbon and hydrogen isotopic compositions were analyzed in the Triassic strata of Moxi gas field in the Sichuan Basin. The natural gases from the second member of the Jialingjiang Formation (T2j2) and the first member of the Leikoupo Formation (T2l1) have dryness coefficients higher than 0.997 and contain low content non−alkane gases such as CO2 and N2. The δ13C1 values of natural gas in the Moxi (MX) gas field range from −35.3‰ to −32.9‰, the δ13C2 values range from −34.0‰ to −30.3‰, and the δD1 values range from −144‰ to −120‰. As for light hydrocarbons composition, the C7 LHs are dominated by the methylcyclohexane (MCH), and the C6−C7 LHs have low normal alkane contents. The individual carbon isotopes of light hydrocarbons have the characteristics of δ13C > −28‰. The origin identification indicates that the natural gas in this area is oil−type gas that results from the secondary cracking of crude oil. Our results show that the natural gas in T2j2 of the MX gas field is sourced from the shale gas of the Є1q, the T2l1 gas is a mixed−source gas from different thermal evolution stages of the Є1q source rocks, shale gas and oil−cracking gas. The mixing effect is the main reason for the reversed phenomenon (δ13C1 > δ13C2).